Geology and genesis of vein-type corundum deposits in the Hafafit-Nugrus area, South Eastern Desert, Egypt - Mahmoud, Soliman Abu Elatta A.; Ali, Hani H. (Geologos, 2020)
Unusual deposits formed by corundum are described from two separate pegmatitic veins in the Hafafit-Nugrus area of the South Eastern Desert of Egypt. Other related minerals are described too. The vein-type of corundum at Locality 1 (Vein 1) crosscuts through exposed rocks of an ophiolitic mélange, whereas at Locality 2 (Vein 2), it crosscuts through exposed serpentinised ultramafic rocks. The main minerals in Vein 1 are plagioclase, corundum, grossular, phlogopite, muscovite and clinochlore, while almandine, xenotime-(Y), allanite-(Ce), zircon, Cr-rich spinel, apatite, titanite, fergusonite-(Y), meta-ankoleite, U-rich thorite (uranothorite), carbonate and illite are the accessories. In Vein 2, the main minerals are plagioclase, corundum, phlogopite and chlorite, while clinochlore, euxenite-(Y), Nb-rich rutile, almandine, xenotime-(Y), allanite-(Ce), zircon, spinel, apatite, titanite, kasolite, dickite, illite, carbonate, antigorite and talc are accessories. The two types of corundum veins differ in their concentrations of Th, U, Zr, Nb, Ta, REE, Y and Li in whole-rock compositions. Field observations, mineralogy and chemical analyses of samples from the two veins of corundum deposits, as well as concentrations of chromophore elements in corundum crystals, suggest metasomatic origins. The present study suggests that the two types of corundum veins formed at different ages from different residual magmas that underwent in-situ hybridisation with the host rocks.